Fenofibrate Protects Cardiomyocytes from Hypoxia/Reperfusion- and High Glucose-Induced Detrimental Effects - Fabiola Cortes-Lopez; Alicia Sanchez-Mendoza; David Centurion; Luz G. Cervantes-Perez; Vicente Castrejon-Tellez; Leonardo del Valle-Mondragon; Elizabeth Soria-Castro; Victoria Ramirez; Araceli Sanchez-Lopez; Gustavo Pastelin-Hernandez; Wylly Ramses Garcia-Niño; Maria Sanchez-Aguilar; et al. (PPAR Research)
Lesions caused by high glucose (HG), hypoxia/reperfusion (H/R), and the coexistence of both conditions in cardiomyocytes are linked to an overproduction of reactive oxygen species (ROS), causing irreversible damage to macromolecules in the cardiomyocyte as well as its ultrastructure. Fenofibrate, a peroxisome proliferator-activated receptor alpha (PPARα) agonist, promotes beneficial activities counteracting cardiac injury. Therefore, the objective of this work was to determine the potential protective effect of fenofibrate in cardiomyocytes exposed to HG, H/R, and HG+H/R. Cardiomyocyte cultures were divided into four main groups: (1) control (CT), (2) HG (25 mM), (3) H/R, and (4) HG+H/R. Our results indicate that cell viability decreases in cardiomyocytes undergoing HG, H/R, and both conditions, while fenofibrate improves cell viability in every case. Fenofibrate also decreases ROS production as well as nicotinamide adenine dinucleotide phosphate oxidase (NADPH) subunit expression. Regarding the antioxidant defense, superoxide dismutase (SOD Cu2+/Zn2+ and SOD Mn2+), catalase, and the antioxidant capacity were decreased in HG, H/R, and HG+H/R-exposed cardiomyocytes, while fenofibrate increased those parameters. The expression of nuclear factor erythroid 2-related factor 2 (Nrf2) increased significantly in treated cells, while pathologies increased the expression of its inhibitor Keap1. Oxidative stress-induced mitochondrial damage was lower in fenofibrate-exposed cardiomyocytes. Endothelial nitric oxide synthase was also favored in cardiomyocytes treated with fenofibrate. Our results suggest that fenofibrate preserves the antioxidant status and the ultrastructure in cardiomyocytes undergoing HG, H/R, and HG+H/R preventing damage to essential macromolecules involved in the proper functioning of the cardiomyocyte.